Chronotype, depression and hippocampal volume: cross-sectional associations from the UK Biobank. (4th May 2019) - Norbury, Ray
ABSTRACT: Diurnal preference for evening time has been associated with increased odds for current depression and a number of indices of the disorder. In the current study, the association between chronotype and depression was explored in a population-based sample of 5360 adults aged between 40 and 70 years. Previous work has also suggested that larger hippocampal volume may be protective against depression. In an additional, exploratory analysis, hippocampal volume was compared in never-depressed early and late chronotypes ( N = 3004). Definite eveningness was significantly associated with increased odds for probable lifetime depression after controlling for a number of confounding factors including neuroticism. Hippocampal volume did not differ between never-depressed early and late chronotypes. The current results extend previous work and add further weight to the argument that late chronotype represents a risk factor for depression.